Specification for control switches (switching devices, including contactor relays, for control and auxiliary circuits, for voltages up to and including 1000 V a.c. and 1200 V d.c.). Additional requirements for rotary control switches Part 2-2.2, (31st January 1977) - British Standards Institution,
No abstract available